2012
DOI: 10.1111/j.1364-3703.2012.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

The Botrytis cinerea cerato‐platanin BcSpl1 is a potent inducer of systemic acquired resistance (SAR) in tobacco and generates a wave of salicylic acid expanding from the site of application

Abstract: Systemic acquired resistance (SAR) is a potent plant defence system that, in response to a first contact with a plant pathogen, prepares the whole plant for subsequent attacks, so that it becomes more resistant to the same and to other pathogens. BcSpl1, a cerato-platanin family protein abundantly secreted by Botrytis cinerea, is required for full virulence and elicits the hypersensitive response in the host. Here, we report that BcSpl1 is also able to induce in tobacco systemic resistance to two plant pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…The involvement of SA signaling in defense response of the MoSM1-OE plants is partially supported by the upregulated expression of OsPR1s and OsPR10 (Figs 1g and 6c), defense genes that are activated by the SA signaling pathway6061, by transiently or stably expressed MoSM1 in rice plants. This is in agreement with the observations that a CP from C. platani in Arabidopsis and BcSpl1 from B. cinerea in tobacco were shown to function through SA signaling4446 but differs from the action of MoMSP1 in rice, in which SA suppressed MoMSP1-induced H 2 O 2 production and cell death in suspension cultured rice cells32. Whereas exogenous SA applied at a high concentration (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The involvement of SA signaling in defense response of the MoSM1-OE plants is partially supported by the upregulated expression of OsPR1s and OsPR10 (Figs 1g and 6c), defense genes that are activated by the SA signaling pathway6061, by transiently or stably expressed MoSM1 in rice plants. This is in agreement with the observations that a CP from C. platani in Arabidopsis and BcSpl1 from B. cinerea in tobacco were shown to function through SA signaling4446 but differs from the action of MoMSP1 in rice, in which SA suppressed MoMSP1-induced H 2 O 2 production and cell death in suspension cultured rice cells32. Whereas exogenous SA applied at a high concentration (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, it has also been shown that CPs from both pathogenic and beneficial biocontrol fungi can induce locally and systemically some structural, physiological and molecular defense responses, including initiation of hypersensitive response (HR), accumulation of phenolic compounds and phytoalexins, production of reactive oxygen species (ROS), and upregulation of defense-related genes in host and nonhost plants33343536373839404142434445. SM1 and SM2 from Trichoderma virens , BcSpl1 from B. cinerea , and MoSM1 (also known as MoMSP1) from M. oryzae could induce systemic disease resistance in rice, cotton, maize, tobacco, tomato and Arabidopsis against different pathogens3237384042454647 and the activation of systemic resistance by CP from C. platani and BcSpl1 from B. cinerea was found to be regulated through stomatal perception, overexpression of salicylic acid (SA)- and ethylene-signaling genes and camalexin biosynthesis4446. Further study revealed that the elicitor activity of the B. cinerea BcSpl1 resides in a two-peptide motif on the protein surface29.…”
mentioning
confidence: 99%
“…PAL accumulation contributes to this assumption, since the corresponding gene product acts as a positive regulator of SA-dependent defense signaling to combat microbial pathogens (Kim and Hwang, 2014). These results in N. tabacum agree with the observations that infiltration of BcSpl1 from B. cinerea leads to the accumulation of SA in tobacco leaves (Frias et al, 2013). Moreover, PR10 is a marker gene for HR-induced cell death, which supports our in vivo observations (Choi et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Orthologues of these genes are also present in B. cinerea ( BcNEP1 and BcNEP2 ) and both proteins are capable of inducing necrosis in the host plants [152]. Cerato-plantanins are small, hydrophobic, secreted proteins found in many fungal phyto-pathogens and have been shown to induce plant defenses leading to systemic acquired resistance [153]. In B. cinerea , cerato-platanin is one of the most abundant secreted proteins and elicits a strong hypersensitive response in the host plant leading to localized necrotic lesions [154].…”
Section: Resultsmentioning
confidence: 99%